FURNITURE ORDERING MARKETPLACE WITH TENDER SYSTEM USING TOPSIS FOR PICKING WINNER RECOMMENDATION - Purwanto, Devi Dwi; Hongary, Kevin - (Research In Management and Accounting (RIMA), 2024)
The use of technology in custom furniture sales is still not utilized to its full potential. A problem is going on inside society, namely that no application helpsthe custom furniture ordering process. There is a problemwhere the buyer has difficulty finding a craftsmanto accept custom furniture according to their wishes in large quantities at competitive prices and quality, and vice versa. Craftsmen had difficulty finding willing buyersto make purchases of custom furniture. This marketplace canhelp with these problems by helping buyersand craftsmen carry out custom furniture transactions safely. Consumers can offer custom orders to craftsmen through the application by stating the specifications, and interested craftsmen can submit offers in terms of price, processing time, quantity, and other agreements, which will be stated in the contract when the transaction occurs. This contract will protect the rights and obligations of customers and craftsmen. On the other hand, consumers are given recommendations for craftsmen using the TOPSIS method, considering the quality of work obtained from the rating, the price offered, working time, and the credibility of the craftsmen's experience.With this marketplace, 60% agree that it makes it easier to bring together customers and craftsmen to make custom furniture. 70% satisfied that the working progress feature helps buyers to know custom furniture progress status and reduce ordering errors. The TOPSIS method helps customers make decisions/selection of craftsmen with a precision of 67.58%.